P183 Impact of patient choice on survival in patients with chronic thromboembolic pulmonary hypertension offered pulmonary endarterectomy. (15th November 2017) - Quadery, SR; Swift, AJ; Billings, C; Thompson, AAR; Elliot, CA; Hurdman, J; Garrod, S; Charalampopolous, A; Sabroe, I; Armstrong, I; Hamilton, N; Sephton, P; et al.
Abstract : Introduction: Chronic thromboembolic pulmonary hypertension (CTEPH) is potentially curable by pulmonary endarterectomy (PEA). Despite this a significant proportion of patients offered PEA decline surgery. Objective: To compare long term survival and prognostic indicators in patients with technically operable CTEPH who underwent PEA and those who declined surgery. Methods: Data were collected for consecutive, treatment-naïve patients diagnosed with CTEPH between 2001 and 2014 identified from the ASPIRE-pulmonary-hypertension-registry. Results: Of 588 patients with CTEPH, 368 patients were offered surgery. Seventy six percent (n=281) underwent PEA, 20% (n=72) declined surgery and 4% (n=15) were planned to undergo surgery. Five year survival was superior in patients undergoing PEA at 83% compared to patients who declined surgery at 56% (p=0.001, log-rank test). In patients who were offered surgery, mixed venous oxygen saturation (SvO2 ) (p=0.003), gas transfer (DLco) (p=0.042), history of coronary artery disease (p=0.031) and patient choice (declining surgery) (p<0.001) were independent predictors of mortality. For patients who declined surgery a median threshold of DLco 62%, right atrial pressure 11 mmHg, and SvO2 62% the positive and negative predictive values for 3 year survival were 31% and 100%, 32% and 95% and 30% and 97%, respectively. Conclusion: In a cohort of consecutive patients with CTEPH the long-term survival of patients undergoing PEA is excellent and superior to patients declining surgery and strongly favours surgical intervention in eligible patients. More work is required to understand factors influencing decision making in CTEPH and to ensure that patients are counselled and supported to make informed decisions.